Aprendizaje por descubrimiento: principios y aplicaciones inadecuadas - Barrón Ruiz, A. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This article deals with a critical analysis of the practical applications of discovery learning. To this end, the principles on which we have reconstructed that theory of learning are used, according to a constructivist foundation of cognitive activity as a conjectural activity, mediated by sociocultural orientations. This article is based on previous research by the author (Barrón 1989, 1991a, 199 I b). After defining and establishing the theoretical principles, the inadequate practical applications of discovery learning are examined, derived, in some cases, from an empiricist concept of discovery, and in others, from a «scientific reductionism», «individualist», or «rnechanistic» concepts of learning by discovery.